Assay for heavy metals using an inhibitive assay based on the acetylcholinesterase from Clarias batrachus - Muhammad, Umar Abubakar; Tham, Lik Gin; Perumal, Natarajan; Mohd Daud, Hassan; Yasid, Nur Adeela; Abd. Shukor, Mohd. Yunus (Hibiscus Publisher, 2016)
Acetylcholinesterase (AChE) is usually used as an inhibitive assay for insecticides. A lesser-known property of AChE is its inhibition by heavy metals. In this work, we evaluate an AChE from brains of Clarias batrachus (catfish) exposed to wastes from aquaculture industry as an inhibitive assay for heavy metals. We discovered that the AChE was inhibited completely by Hg2+, Ag2+, Pb2+, Cu2+, Cd2+, Cr6+ and Zn2+ during initial screening. When tested at various concentrations, the heavy metals exhibited exponential decay type inhibition curves. The calculated IC50 (mg/L) for the heavy metals Ag2+, Cu2+, Hg2+, Cr6+ and Cd2+ were 0.088, 0.078, 0.071, 0.87 and 0.913, respectively. The IC50 for these heavy metals are comparable, and some are lower than the IC50 values from the cholinesterases from previously studied fish. The assay can be carried out in less than 30 minutes at ambient temperature.